Heteroatom facilitated preparation of electrodes for sodium ion batteries - Bhosale, Manik E.; Banerjee, Abhik; Krishnamoorthy, Kothandam (RSC Advances, 2017)
A conjugated polymer comprising heterocycles was prepared and carbonized to obtain carbon with interlayer spacings between 0.42 and 0.37 nm and exhibited a specific capacity of 250 mA h g(-1).